The Geography of Intergenerational Mobility in Latin America and the Caribbean - Munoz Saavedra, Ercio Andres (Washington, DC: World Bank, 2022)
This paper estimates intergenerational mobility in education using data from 91 censuses that span 24 countries in Latin America and the Caribbean over half a century. It measures upward mobility as the likelihood of obtaining at least a primary education for individuals whose parents did not finish primary school, whereas downward mobility is the likelihood of failing to complete primary education for individuals whose parents completed at least primary school. In addition, the paper explores the geography of educational intergenerational mobility using nearly 400 “provinces” and more than 6,000 “districts”. It documents wide cross-country and within-country heterogeneity. The paper documents a declining trend in the mobility gap between urban and rural populations, and small differences by gender. Within countries, the level of mobility is highly correlated with the share of primary completion of the previous generation, which suggests a high level of inertia. In addition, upward (downward) mobility is negatively (positively) correlated with distance to the capital and the share of employment in agriculture, but positively (negatively) correlated with the share of employment in industry.